Hubungan Pemberian Mp-Asi Oleh Ibu Primipara Terhadap Status Gizi Baduta Usia 6-24 Bulan - Usman; Wahdaniyah; Justiyulfah (Nutrition Science and Health Research, 2023)
Primipara is a woman who gave birth for the first time and had her first child. Primaripara mothers are usually not ready to play a role in taking care of babies. One of the access to overcome baby care is through health services that are easily accessible to the community with programs to improve maternal knowledge and skills. The purpose of the study was to determine the relationship between MP-ASI feeding behavior by primipara mothers and nutritional status. Research Methods with instruments using questionnaires, total sampling techniques with a total of 39 respondents. The results of the study showed a p-value of >0.005 which means that there was no relationship between the behavior of breastfeeding MP by primipara mothers and the nutritional status of clowns aged 6-24 months in Pambusuang village. The conclusion of this study which includes the relationship of knowledge, attitudes, and actions of MP breastfeeding by primipara mothers to nutritional status where the results of the study have a p-value of >0.005. The results showed that there was no relationship between the behavior of MP breastfeeding by primipara mothers and the nutritional status of clowns aged 6-24 months in Pambusuang village, Polewali Mandar Regency.